Teachers' Collective Efficacy as a Predictor of Students' Academic Performance in North Central Nigeria - Yusuf Laro Ibrahim; Yunus Adebunmi Fasasi; Mustapha Adam Ishola; Yusuf Suleiman (Ignatianum University Press, 2021)
Public secondary schools in Nigeria occupy a significant position for providing qualitative education, yet there has been increasing public discontent with the quality of students being produced in the country's public secondary schools. Teachers are regarded as one of the resources necessary for achieving the goals of secondary education. It is against this backdrop that this study examined teachers' collective efficacy as a predictor of students' academic performance in North Central Nigeria. Three research questions and hypotheses were generated to guide the study, which made use of a correlation-type descriptive research design with a population consisting of all teachers in the North Central region. An instrument titled the Teachers' Collective Efficacy Questionnaire (TCEQ) was developed to elicit pertinent data from the participants. Also, students' academic achievement was measured. The results of the study revealed that no substantial nexus existed between the teachers' experience and the students' academic achievement. However, the teachers' verbal encouragement was found to be an important predictor of the learners' academic success. Similarly, the teachers' academic emphasis was a significant predictor of the learners' academic performance. Based on this, it was established that teachers' collective efficacy is an important predictor that can be used to improve students' academic achievement. The study recommended that education administrators should acquaint their staff with the importance of collective efficacy towards improving students' academic performance. It was also recommended that the government should organize workshops, seminars, and conferences for the supervisors, principals, and teachers of schools on efficacy issues and that teachers should be well motivated to maintain a high degree of efficacy in their various schools.